2014
DOI: 10.1037/prj0000087
|View full text |Cite
|
Sign up to set email alerts
|

The economic status of parents with serious mental illness in the United States.

Abstract: Objective Parents with serious mental illness may be vulnerable to financial insecurity, making successful parenting especially difficult. We explored relationships among parenting, serious mental illness and economic status in a nationally representative sample. Methods The sample included all working-age participants from the 2009 and 2010 National Survey on Drug Use and Health (n = 77,326). Two well-established scales of mental health distinguished participants with none, mild, moderate, and serious menta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
34
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(34 citation statements)
references
References 27 publications
0
34
0
Order By: Relevance
“…), whereas only one of four men with severe mental illness is actually parenting (Luciano et al . ).…”
Section: Introductionmentioning
confidence: 97%
“…), whereas only one of four men with severe mental illness is actually parenting (Luciano et al . ).…”
Section: Introductionmentioning
confidence: 97%
“…Internationally, rates of maternal mental illness range anywhere from 7.5% in Australia (Buist et al, ) to 38% in the USA (Luciano, Nicholson, & Meara, ). Abel et al () found that Northern Ireland (NI) had the highest levels of maternal mental illness in the UK; with one in four children, aged 0–16 years, exposed to maternal mental illness and 53% of children over 16 having a mother who has been diagnosed with a common (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…These latter factors are known contributors to parenting problems in the general population, for which there are already some welldeveloped evidence-based interventions. Luciano et al (2014) found that parents with a SMI, compared to parents without a SMI, were less economically stable and more likely to fall below the poverty line [5]. Poverty and unemployment are two major issues associated with child welfare involvement and both generate additional risks such as housing instability, inaccessible healthcare, and community violence [6].…”
mentioning
confidence: 99%